2022
DOI: 10.3390/jcm11030607
|View full text |Cite
|
Sign up to set email alerts
|

TROP2 Expression in Sebaceous and Sweat Gland Carcinoma

Abstract: Sebaceous carcinoma and sweat gland carcinoma (malignant tumors with apocrine and eccrine differentiation) are rare malignant skin adnexal tumors that differentiate toward sebaceous gland and eccrine and apocrine glands, respectively. Owing to the rarity of these carcinomas, standard treatments for advanced disease have not been established. Because the prognosis of patients with systemic metastasis is poor, a new treatment for these diseases is eagerly desired. Trophoblast cell surface antigen 2 (TROP2) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…The mean H-score for the sebaceous carcinoma group in our study was 258.1, which is nearly identical to that seen in their study. 23 We further documented Nectin-4 expression in two other rare types of cutaneous adnexal carcinomas: digital papillary adenocarcinomas and squamoid eccrine ductal carcinomas. In our study, the level of Nectin-4 expression in these two adnexal carcinomas appeared to be significantly less than that in sebaceous carcinomas.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The mean H-score for the sebaceous carcinoma group in our study was 258.1, which is nearly identical to that seen in their study. 23 We further documented Nectin-4 expression in two other rare types of cutaneous adnexal carcinomas: digital papillary adenocarcinomas and squamoid eccrine ductal carcinomas. In our study, the level of Nectin-4 expression in these two adnexal carcinomas appeared to be significantly less than that in sebaceous carcinomas.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have reported Nectin‐4 to be highly expressed in melanomas, 21 squamous cell carcinomas, 22 and extramammary Paget disease 14 . Most recently, Nectin‐4 was reported to be frequently expressed in sebaceous carcinomas and sweat gland carcinomas (types unspecified) 23 . Their study included 14 cases of sebaceous carcinoma and 18 cases of sweat gland carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FDA-approved ADCs for solid tumors include trastuzumab emtansine and trastuzumab deruxtecan (anti-HER2 ADCs) for breast cancer, enfortumab vedotin (anti-NECTIN-4 ADC) for urothelial cancer, sacituzumab govitecan (anti-TROP-2 ADC) for breast cancer, and tisotumab vedotin (anti-tissue factor ADC) for cervical cancer. Interestingly, NECTIN-4 and TROP-2 are highly expressed in normal skin and its appendages, as well as in various skin cancers [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], and anti-NECTIN-4 ADC might be a candidate for unresectable skin cancers, including NAM. Several melanoma-specific ADCs are currently undergoing preclinical and clinical trials.…”
Section: Treatmentmentioning
confidence: 99%